Solubility and crystal growth of sodium nitrate from mixed alcohol – water solvents - Rossiter, Angelina Jane (Curtin University, 2009)
Due to the ductile nature of the sodium nitrate crystal which deforms plastically under high levels of strain, most of the crystal growth studies in aqueous solution have focussed on the influence of tensile strain, supersaturation and dislocation, using x-ray surface topography to characterise the dislocation structure of the crystal. Most of the crystal growth studies have also focussed on growth from the melt since single crystals of sodium nitrate find application in optical pumping experiments, are a potential substitute for calcite in the preparation of polarising prisms and are interesting for the study of plastic properties because two types of plastic deformation, glide and twinning, take place in these crystals at room temperature. Its crystal habit is also difficult to modify and many researchers have used dyes to investigate its effect. Sodium nitrate is also a highly soluble substance with 96g of sodium nitrate dissolving in 100g of water at 30.0°C, making aqueous solutions of this salt and its supersaturation extremely unstable. Literature on its solubility in organic solvents, such as methanol, ethanol and isoproponal, are quite outdated and limited to specific conditions.This study involved the determination of the solubility of sodium nitrate in aqueous methanol, ethanol and isopropanol solutions at different temperatures and weight percents of the organic solvents. Splitting into two liquid phases was observed when using isopropanol, however this phase separation does not occur at low and high mass fractions of alcohol, as at lower concentrations of one solvent the two solvents are miscible. Whereas in the presence of methanol and ethanol the solubility of sodium nitrate in water was significantly reduced, with the solubility decreasing with increasing molecular weight of the alcohol. The experimental data for methanol and ethanol was used for the determination of the ion-specific Non random two liquid (NRTL) parameters by correlating with the modified extended NRTL model. It was observed for both methanol and ethanol that the model was found to satisfactorily correlate the data at low to moderate concentrations of alcohol. However, as the concentration of alcohol rises the model prediction was found to be less satisfactory, probably due to the interaction parameters of NRTL between alcohol and the ions not being able to represent the low solubility of electrolytes.The growth rates of individual faces of sodium nitrate crystals grown in situ in a batch cell and observed with an optical microscope were measured at different temperatures (20.0, 30.0 and 40.0°C) and relative supersaturations (0.02, 0.04, 0.06, 0.08 and 0.1) to determine the kinetics of growth for homogeneous nucleation. A combined growth order, of 1, and activation energy of 23,580 J/mol was obtained indicating that crystal growth in these sets of experiments was diffusion controlled. Crystal growth rates were also obtained for sodium nitrate crystal seeds grown at 20.0°C at a supersaturation of 0.02 and 0.04, in a modified growth cell where the saturated solution was circulated at a flow rate of 4mL/min. The crystal growth rates obtained were much lower in comparison to the growth rates obtained by homogeneous nucleation. In both sets of experiments size independent growth was observed.The surface morphology of the crystals was also observed by optical microscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM) for the crystals grown by homogeneous nucleation to elucidate the mechanism of growth. Liquid inclusions were observed by optical microscopy for crystals that were grown at high temperatures and for a long duration. SEM revealed the presence of pitting on the crystal surface due to the high solubility of sodium nitrate, while AFM images showed the presence of growth hillocks which suggests that crystal growth is surface integration controlled. However, the presence of growth hillocks could have been caused by the formation of some nuclei and surface artefacts when the crystal was taken out from solution. In seeded crystal growth experiments the solute was observed by optical microscopy to deposit onto the crystal surface.The effect of solvent composition on the growth rate and habit modification of sodium nitrate was also investigated with aqueous solutions of methanol and ethanol. Crystal growth rates of sodium nitrate crystals grown in situ in a batch cell by homogeneous nucleation in aqueous ethanol at 30.0°C at 20, 50 and 90 weight percent of ethanol and crystal seeds grown at 20.4°C at a supersaturation of 0.02 and 0.04 at 30, 50 and 90 weight percent of ethanol, in a modified growth cell was measured. It was found that growth rates decrease with increasing amounts of ethanol and the habit of the crystal remains unchanged. The growth rate was also observed to be much lower than the growth rates obtained from pure aqueous solution. For crystals grown by homogeneous nucleation it was observed that with increasing supersaturation, decreasing weight percent of ethanol and with increasing crystal size the number of liquid inclusions observed on the crystal surfaces increased, whereas for seeded crystal growth solute was observed to deposit on to the crystal surface mainly at low alcohol weight percents. Sodium nitrate crystals grown in aqueous methanol was also observed to behave similarly to crystals grown in ethanol, with lower growth rates obtained. For all cases size independent growth was observed.The influence of additives, DOWFAX 3B2 and amaranth was also investigated on the habit modification of sodium nitrate for crystals grown by homogeneous nucleation at 20.0°C at a supersaturation of 0.04. Both additives were observed to be effective in changing the crystal habit of sodium nitrate, with the appearance of triangular truncations or octahedral facets at the corners of the sodium nitrate crystal due to the additive being adsorbed onto the crystal surface. The influence of the additives on the crystal habit modification can be explained due to the presence of the anionic polar group, the sulphonate group. The growth ratio value for DOWFAX 3B2 was also found to decrease with increasing additive concentration.It is believed that the results of this thesis provides up to date data on the solubility of sodium nitrate in aqueous ethanol and for temperatures and weight percents that have not been reported before in literature for the aqueous methanol system. The work reported on crystal growth studies by homogeneous nucleation and using crystal seeds, the effect of solvent and DOWFAX 3B2 on crystal growth rates and habit modification is also new and has not been reported in literature before.